2022
DOI: 10.3390/bios12090721
|View full text |Cite
|
Sign up to set email alerts
|

An Interplay between Lossy Mode Resonance and Surface Plasmon Resonance and Their Sensing Applications

Abstract: Conducting metal oxide (CMO) supports lossy mode resonance (LMR) at the CMO-dielectric interface, whereas surface plasmon resonance (SPR) occurs at the typical plasmonic metal-dielectric interface. The present study investigates these resonances in the bi-layer (ITO + Ag) and tri-layer (ITO + Ag + ITO) geometries in the Kretschmann configuration of excitation. It has been found that depending upon the layer thicknesses one resonance dominates the other. In particular, in the tri-layer configuration of ITO + Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The simultaneous generation of LMR and SPR resonances on a same planar platform has been reported by Fuentes et al 27 and further Gaur and colleagues 44 investigated the interplay of these optical phenomena and the dependence of one to another from a theoretical and practical point of view, by studying bilayers of ITO and Ag and trilayers ITO-Ag-ITO, exploring different thicknesses and reporting how the sensitivity varies in the different layer configurations 44 . It resulted that depending on the layer thicknesses one resonance dominates the other 44 .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The simultaneous generation of LMR and SPR resonances on a same planar platform has been reported by Fuentes et al 27 and further Gaur and colleagues 44 investigated the interplay of these optical phenomena and the dependence of one to another from a theoretical and practical point of view, by studying bilayers of ITO and Ag and trilayers ITO-Ag-ITO, exploring different thicknesses and reporting how the sensitivity varies in the different layer configurations 44 . It resulted that depending on the layer thicknesses one resonance dominates the other 44 .…”
Section: Discussionmentioning
confidence: 74%
“…The simultaneous generation of LMR and SPR resonances on a same planar platform has been reported by Fuentes et al 27 and further Gaur and colleagues 44 investigated the interplay of these optical phenomena and the dependence of one to another from a theoretical and practical point of view, by studying bilayers of ITO and Ag and trilayers ITO-Ag-ITO, exploring different thicknesses and reporting how the sensitivity varies in the different layer configurations 44 . It resulted that depending on the layer thicknesses one resonance dominates the other 44 . In the present work, it was demonstrated that a POF modified with bilayers of ZrO 2 –TiO 2 or TiO 2 –ZrO 2 and followed by a gold layer 30 , provided LMR and SPR and can be used in combination with highly selective, soft nanoMIPs to develop a new, cheap and ultralow sensitive sensing platform.…”
Section: Discussionmentioning
confidence: 74%
“…Adding dopants, impurities, composite structures, or metal additives can further manipulate the charge transfer in a SMOx. In addition to improving the long-term stability and selectivity, these components lower the operation temperature, energy consumption, and humidity interference of pristine SMOx [ 19 , 20 , 21 , 22 , 23 ]. There are two types of SMOx materials: n-type and p-type, depending on the type of dopants.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of their tunable sensitivity, selectivity, and response time, SMOx-based materials are widely used in sensors that detect gases, chemicals, and biomolecules. With SMOx-based sensors, a wide range of gases can be detected, such as oxidizing gases and reducing gases [ 17 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gaur et al investigated the interplay between SPR and lossy mode resonance (LMR) in this Special Issue. They compared these two types of sensing techniques in terms of sensitivity, detection accuracy, and figure of merit [ 23 ]. The SPR effect is a complicated physical phenomenon that occurs when light strikes a conductive layer of noble metal.…”
mentioning
confidence: 99%